(untitled) (Fiep Bulletin - online, 2014)
Swimming, with its impact on human body is one of the most effective ways for developing of physical and functional capabilities with immediate and long-term effects. Testing the level of the swimming capabilities reveals non-swimmer or swimmers beginners. Swimming and swimming sports at the universities are included in the curriculum in physical education syllabus. Swimming at these faculties is based on a voluntary choice. This option also has the students of FM PI CU Bratislava. First-year students can choose according to their content of hours of self-interest (sports games, hiking, aerobics, swimming, etc.). Department of Physical Education at FCHFT includes swimming as a compulsory subject in the context of physical education in the curriculum. The aim of our research is to monitor the level of the swimming abilities of FCHFT STU and FM PI CU students by the test 100 m free style swimming. Tracking research was conducted in the school year 2012/2013. The group consisted of randomly selected students FCHFT STU and FM PI CU Bratislava. Along with testing involving about 600 students from which we randomly selected 60 students from each faculty (28 men a 32 women from FCHFT STU and 38 men and 22 women from FM PI CU ). Swimming standard time for men is 136.73 sec and women 172.4 sec (Macejková, Ben?uriková, 2003). The best FM PI men time was 79 sec and women 97 sec. The best FCHFT men and women time was 60 sec. Average FM PI CU men time was 114.53 sec., women 131.68 and FCHFT STU men time was 123.43 sec and women 118.81. In all our groups students achieve better time than the swimming standard is.